Pengaruh Profitabilitas dan Solvabilitas Terhadap Harga Saham Sektor Agriculture Di BEI Tahun 2017-2020 - Muhammad Iftitahu Khoiron; Tony Seno Aji (Jurnal Ekonomika : INDEPENDEN, 2022)
This study aims to examine the effect of Profitability (ROA) and Solvency (DER) ratios on Stock Prices in the Agriculture sector listed on the Indonesia Stock Exchange (IDX) 2017-2020. The method of selecting the sample taken is purposive sampling with the criteria of companies listed on the Indonesia Stock Exchange (IDX) in the Agriculture sector that were not delisted and provided the information needed during 2017 to 2020 in a row, there were 16 companies according to the criteria. The analysis technique used is multiple linear regression. The results of this study conclude that simultaneously ROA and DER have a significant effect on stock prices. While partially, only ROA variable is significant to stock prices in a positive direction, while the DER variable has no effect on stock prices of Agriculture companies on the Indonesia Stock Exchange.